The training and praxis of the nurse in the light of nursing theories - Bruna Pegorer Santos (Revista Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to report the experience of the development of nursing knowledge from nursing theories and points of contact with the nurse’s praxis. Method: case report on the reflections on contents addressed in the discipline offered in the Graduate Program in Nursing in a federal public university. The students presented seminars approaching the main nursing theories, generating extensive discussion and correlating them with the nurse’s practice. Review and reflection on the contents addressed. Result: two themes were defined: the training of nursing undergraduate students and the development of knowledge in relation to the concepts of nursing theories; and care models and nurses’ critical reasoning about the applicability of nursing theories. Final Consideration: the reflections produced permeated the development and acquisition of knowledge and of representative meanings of healthcare practice from the assumptions and constructs of the theories.